2022
DOI: 10.17214/gaziaot.905517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of First Permanent Molar Extractions Due to Caries in Children

Abstract: Bu çalışmanın amacı; çocuklarda çürük nedeniyle çekilen birinci büyük azı dişlerinin çekim sıklığının ve çekim öncesi tedavi görme durumunun belirlenmesidir. GEREÇ VE YÖNTEM: Bu çalışmada 7-14 yaş arası 858 hastanın 3,432 birinci büyük azı dişi panoramik radyografiler üzerinde değerlendirildi. Dişlerin mevcut ve geriye dönük durumlarının belirlenmesinde klinik kayıtlar ve fakülte arşivinde yer alan hasta anamnez formlarından faydalanıldı. Hastaların cinsiyeti, çekilmiş veya çekim endikasyonu konulmuş birinci b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…22 In permanent denti- In a study conducted by Tokuç and Çelik, 6.8% of children had been diagnosed as requiring the extraction of at least one permanent molar tooth due to caries, a rate considerably higher than in the results of our study. 23 Extraction may be the only option for severely affected MIH molars, which have a poor long-term prognosis. 24 Albadri et al reported that after caries the 2 nd most frequent cause of permanent first molar tooth extraction was MIH, with a rate of 11%; this is similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…22 In permanent denti- In a study conducted by Tokuç and Çelik, 6.8% of children had been diagnosed as requiring the extraction of at least one permanent molar tooth due to caries, a rate considerably higher than in the results of our study. 23 Extraction may be the only option for severely affected MIH molars, which have a poor long-term prognosis. 24 Albadri et al reported that after caries the 2 nd most frequent cause of permanent first molar tooth extraction was MIH, with a rate of 11%; this is similar to our study.…”
Section: Discussionmentioning
confidence: 99%